2008
DOI: 10.1017/s000748530800624x
|View full text |Cite
|
Sign up to set email alerts
|

Population fluctuations of light-attracted chrysomelid beetles in relation to supra-annual environmental changes in a Bornean rainforest

Abstract: In Southeast Asian tropical rainforests, two events, severe droughts associated with the El Niño-Southern Oscillation and general flowering, a type of community-wide mass flowering, occur at irregular, supra-annual intervals. The relationship between these two supra-annual events and patterns of insect population fluctuations has yet to be clearly elucidated. Leaf beetles (Chrysomelidae) are major herbivores and flower-visitors of canopy trees, affecting their growth and reproduction and, in turn, affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…The degree of inter-vs. intra-annual variation in tropical insect communities has rarely been assessed. A short-term study of beetle populations in Borneo found inter-annual variation to greatly exceed intra-annual variation, which supported the characterization of this rainforest as generally aseasonal with a strong ENSO effect (Kishimoto-Yamada et al 2009). …”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…The degree of inter-vs. intra-annual variation in tropical insect communities has rarely been assessed. A short-term study of beetle populations in Borneo found inter-annual variation to greatly exceed intra-annual variation, which supported the characterization of this rainforest as generally aseasonal with a strong ENSO effect (Kishimoto-Yamada et al 2009). …”
Section: Introductionmentioning
confidence: 66%
“…During the studied years, the highest annual precipitation occurred in 2001 (not coinciding), followed by 2006, 2003, and 2010 (all coinciding with the positive El Niño phases). Previously, the effects of an ENSO event (severe droughts and consequent synchronous flowering and leaf-production in Southeast Asian rainforests) on insect communities have been reported in several short-term studies (Harrison 2000, Intachat et al 2001, Kishimoto-Yamada et al 2009). In Central-America, the ENSO has been associated with increases in the migrating adults of a butterfly species via increased soil moisture and leaf flushing of the host plants (Srygley et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huberty and Denno 2004;Kishimoto-Yamada and Itioka 2008;Scherber et al 2013). Conversely, individual species may show a sudden proliferation following a drought (Kishimoto-Yamada et al 2009;van Bael et al 2004). Without data on community composition prior to the event, the impact of such climatic extremes on our results is difficult to judge.…”
Section: Discussionmentioning
confidence: 89%
“…The leaf and flower production of many dipterocarp trees is known to fluctuate synchronously among species at irregular intervals [13, 14, 2123]. In contrast, the adults of some leaf chewer species emerge constantly throughout the year and fluctuate in abundance independently of dipterocarp tree phenology [23,24], although they have been observed to feed on the young leaves and flowers of dipterocarp trees [25]. This pattern leads us to hypothesize that these leaf chewer species are able to feed on other plant species when the young leaves and flowers of dipterocarp trees are unavailable.…”
Section: Introductionmentioning
confidence: 99%